DETERMINANTS OF MANAGEMENT EFFECTIVENESS OF SCHOOL OPERATIONAL ASSISTANCE FUNDS (BANTUAN OPERASIONAL SEKOLAH/BOS) AT SDN KALIGLAGAH 04 - Nur Lailatus Subha; Suwignyo Widagdo; Nurshadrina Kartika Sari (LPPM Institut Teknologi dan Sains Mandala, 2023)
This study aims to analyze the effect of applying the principles of accountability, transparency, and stakeholder’s participation on the effectiveness of the management of School Operational Assistance Funds (BOS/Bantuan Operasional Sekolah) at SDN Kaliglagah 04 Sumberbaru District. The method used in this research is by distributing questionnaires. We used 80 sample in this study, they were school committee, teachers and parents. The sampling technique was carried out by simple random sampling technique. The data analysis method used is Multiple Linear Regression. The results showed that transparency had a partial effect on the effectiveness management of the School Operational Assistance Funds (BOS). While the application of the principle of accountability and stakeholder participation does not partially affect the effectiveness of the management of School Operational Assistance Funds (BOS). Simultaneously the application of the principles of accountability, transparency and stakeholder participation affect the effectiveness of the management of School Operational Assistance Funds (BOS).